Optimizing the chain of dissertation councils in Russia - L. A. Tsvetkova; O. A. Yeremchenko; F. A. Kurakov (Ekonomika Nauki)
The article explored outcomes of optimizing a network of dissertation councils in Russia in the period between 2013 and 2015 years. The subject structure of world science was compared with anticipated after optimization disciplinary structure of highly qualified Russian scientific personnel body. To make the comparison completed, there was evaluated the gravity of publication flow volume per certain subjects in data bases like Web of Science and the contribution of certain related areas in forming research frontlines according to data of Essential Science Indicators. It was factually proven that project's realization contributes to the process of balancing out the structure of reproduced body of highly qualified personnel in Russia and of the world's science subject structure. In addition to that, it was noted that by the end of 2015 year Russia will witness a groundlessly low share of dissertation councils in medicine and similarly groundlessly in the context of global science development trends a high share of councils in economics sciences.